Factors of innovative behavior affecting Indonesian lecturers' contextual and task performance - Ririn Handayani; Widodo Widodo; Umalihayati; Megawati Megawati; Jafriansen Damanik; Saptana Tri Prasetiawan (Knowledge & Performance Management, 2025)
This study aims to explore the innovative behavior mediation mechanism to illuminate Indonesian lecturers’ contextual and task performance from the perspectives of talent management, learning organizations, and grit. Three hundred eighty-five lecturers from Indonesian private universities were inadvertently sampled using a Likert scale questionnaire to gather research data. The structural equation modeling method was used to examine the collected data. The results indicated that talent management, learning organization, and grit significantly affect lecturers’ innovative behavior; innovative behavior, in turn, influences lecturers’ contextual and task performance, and talent management, learning organization, and grit also significantly affect lecturers’ contextual and task performance through innovative behavior. Grit has a more substantial influence on lecturers’ innovative behavior than others. It also indirectly influences contextual and task performance through innovative behavior, which is more vital than talent management and learning organizations. This suggests that individual internal factors (grit) tend to have a more substantial influence on individual variables (innovative behavior and performance) than external factors (talent management and learning organizations). In conclusion, this evidence highlights that innovative behavior is crucial in transmitting talent management, learning organization, and grit into lecturers’ contextual and task performance. It provides a new empirical model that theoretically advances studies of higher education management, particularly those concerning the connection between talent management, learning organization, and grit with lecturers’ contextual and task performance through innovative behavior. The findings have practical implications for higher education practice, particularly in improving lecturers’ contextual and task performance through the lenses of talent management, learning organization, grit, and innovative behavior.